The survey of the status of self-stigma of depression and its relationship with demographic factors in Gonabad, Iran - Tehrani, Hadi; Naddafi, Fatemehzahra; Nejatian, Mahbobeh; Jafari, Alireza (Frontiers in Psychiatry, 2024)
IntroductionDepression is a common mental illness. Depression stigma can reduce individuals’ desire to seek mental health services. No study has investigated depression self-stigma and its relationship with demographic factors in the general population of Gonabad city in Iran. Therefore, this study was aimed at determining the relationship between depression self-stigma and demographic factors.MethodsThis cross-sectional study was conducted among 1,075 Iranians living in Gonabad city in 2024. Proportionate stratified sampling was used to select participants. Data collection tools included demographic data and the self-stigma of depression scale (SSDS). Higher SSDS scores indicate greater depression self-stigma. Data were analyzed using SPSS 24 with the independent samples t-test, one-way analysis of variance, and Pearson correlation.ResultsThe mean (± SD) of self-stigma of depression (SSD) was 42.51 (9.31). Only 16.1% of the participants mentioned that they had a mental disorder, and 17.2% reported that they had been referred to a psychologist. Based on the results, males had more SSD (p = 0.028), help-seeking inhibition (p < 0.001), and shame (p = 0.002) than females. There were no significant relationships between education level, economic status, age group, occupation, and marital status with SSD (p > 0.05). Individuals with a history of mental disorder had higher SSD (p = 0.011) and help-seeking inhibition (p = 0.004). People who did not obtain information related to mental illness had more help-seeking inhibition (p = 0.001). Based on the Pearson correlation results, a positive and significant correlation coefficient was observed between the subscales of SSDS (P < 0.001).ConclusionThe results of the study showed that SSD level was 42.51 ± 9.31 from 70. SSD is one of the main obstacles to help-seeking and treatment, so providing knowledge and awareness in this area is essential to the community.